COMPARISON OF PHYSIOLOGICAL PARAMETERS IN CHILDREN UNDERGOING DENTAL TREATMENT UNDER GENERAL ANESTHESIA WITH PROPOFOL AND SEVOFLURANE - A RETROSPECTIVE COHORT STUDY - G, Lavanya; Gurunathan, Deepa; Krishnan, Navaneetha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present study was conducted to evaluate the effect of these drugs on the blood pressure (BP) and pulse rate during induction of anesthesia in children undergoing full mouth rehabilitation. Methods: Data were collected from the records maintained for the children <6 years who underwent full mouth rehabilitation under general anesthesia (GA). The drugs used for induction, the changes seen in the BP, pulse rate were recorded. Statistical analysis was done using Mann–Whitney test with p<0.05, significant. Results: Of 64 children treated under GA, 31 children were induced with propofol and by sevoflurane in the remaining 33 children. The induction time with 2 mg/kg dosage of propofol was approximately 12 seconds while it was variable with 8% sevoflurane. The mean systolic and diastolic BP and pulse rate were found to be within the normal levels under both the drugs. Conclusion: In children, sevoflurane and propofol can be safely used for inducing anaesthesia.